Answer:
x + 5 = 5
Step-by-step explanation:
Solution doesn't change as the x in the equation is 0 and the answer totals as 5 due to 5 plus 0 being 5
Answer:
The sale price is 
The expression is 
Step-by-step explanation:
we know that
The sale price is equal to subtract the discount price from the original price
The discount price is equal to multiply the original price by the percent discount in decimal form
Let
x ----> the sale price
y ---> discount price
----> percent discount in decimal form


substitute

therefore
the expression is

The answer is actually choice A
---------------------------------------------------------
---------------------------------------------------------
If we add up the equations straight down we will have 0a+2b = 6
Note how adding the 'a' terms gives us 3a + (-3a) = 3a-3a = 0a. The 0a term is really 0 since 0 times anything is 0. So the 'a' terms will go away
The equation 0a+2b = 6 turns into 0+2b = 6 and that simplifies to 2b = 6
To isolate b, we divide both sides by 2
2b = 6
2b/2 = 6/2
b = 3
We can stop here since only one answer choice has b = 3, which is choice A. However, let's keep going to find the value of 'a'
Plug b = 3 into any equation with 'a' and 'b', then solve for 'a'
3a+4b = 9
3a+4*3 = 9
3a+12 = 9
3a+12-12 = 9-12
3a = -3
3a/3 = -3/3
a = -1
So a = -1 and b = 3 pair up to form (a,b) = (-1,3)
--------------------------------------
To check, plug this ordered pair back into both equations
Equation 1:
3a+4b = 9
3*(-1)+4*3 = 9
-3+12 = 9
9 = 9
Equation 1 has been checked out
Equation 2:
-3a-2b = -3
-3(-1)-2(3) = -3
3 - 6 = -3
-3 = -3
this is true as well
So this confirms that the final answer is choice A
Answer:
13.1148770486
.....................,...
Answer:find the solution to the system of equations below.start by adding the equation
{-2x+2y=-8
{2x+y=5
Step-by-step explanation:The given system of equation are:
1---- y= x -4
2----- y=4 x+2
Equation (1) - Equation (2)
→0= x -4 - (4 x+2)
→0= -3 x -6-----[Adding and subtracting like terms]
Adding 3 x on both sides
→3 x= -6
Dividing by 3 on both sides
→x = -2
→Substituting the value of x in equation 1, we get
y= -2 -4
y =-6
→Solution set =(x,y)=(-2, -6)
Don't used the graph to find the solution.